The Circadian Clock in Oral Health and Diseases. (January 2014) - Papagerakis, S.; Zheng, L.; Schnell, S.; Sartor, M.A.; Somers, E.; Marder, W.; McAlpin, B.; Kim, D.; McHugh, J.; Papagerakis, P.
Most physiological processes in mammals display circadian rhythms that are driven by the endogenous circadian clock. This clock is comprised of a central component located in the hypothalamic suprachiasmatic nucleus and subordinate clocks in peripheral tissues. Circadian rhythms sustain 24-hour oscillations of a large number of master genes controlling the correct timing and synchronization of diverse physiological and metabolic processes within our bodies. This complex regulatory network provides an important communication link between our brain and several peripheral organs and tissues. At the molecular level, circadian oscillations of gene expression are regulated by a family of transcription factors called "clock genes". Dysregulation of clock gene expression results in diverse human pathological conditions, including autoimmune diseases and cancer. There is increasing evidence that the circadian clock affects tooth development, salivary gland and oral epithelium homeostasis, and saliva production. This review summarizes current knowledge of the roles of clock genes in the formation and maintenance of oral tissues, and discusses potential links between "oral clocks" and diseases such as head and neck cancer and Sjögren's syndrome.